11z-5z+6=-24-9z

Simple and best practice solution for 11z-5z+6=-24-9z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11z-5z+6=-24-9z equation:



11z-5z+6=-24-9z
We move all terms to the left:
11z-5z+6-(-24-9z)=0
We add all the numbers together, and all the variables
11z-5z-(-9z-24)+6=0
We add all the numbers together, and all the variables
6z-(-9z-24)+6=0
We get rid of parentheses
6z+9z+24+6=0
We add all the numbers together, and all the variables
15z+30=0
We move all terms containing z to the left, all other terms to the right
15z=-30
z=-30/15
z=-2

See similar equations:

| x=60-0.3(40-0.2x) | | 7k-(-16)=65 | | 30=-x/5+15 | | 17=-5-w | | 8p+3=35 | | x=400+0.8(350+0.7x) | | (n-6)^2=0 | | 33=3y-42 | | -5=10+5r | | 45/x=12/100 | | x/5+10=-12 | | y=350+0.7(400+0.8y) | | 0.6x+0.5=1.16666 | | 0.5(x+8)-15=-13 | | 2p+47=95 | | 19-5/2m=34 | | 2(4x+1)=5x-8 | | 21z-3=3z+6 | | 5h+2(h+11)=3(h+2) | | 1/2m-5=-3/2 | | 6w=6840 | | -8-3x=0 | | .2-2k=0.9 | | 12-7y+7y=12 | | 6(x+8)=−36 | | (4x9)/6+10= | | (x−2)=−48 | | 25-4x=-11 | | 5x=12x+36 | | 10z+21=15-2z | | 4p^2=4 | | 9(-8)+9y=9 |

Equations solver categories